New Expanding Flexible Ring-type Overrunning Clutch - Du Li; Wei Dong; Chen Kui; Song Zelian (Jixie chuandong)
During the design process of the overrunning clutch,on the basis of flexible ring- type overrunning clutch which is based on the traditional flexible body- friction typed Euler formula,the physical model of Euler formula is innovatively extended and a new overrunning clutch- expanding flexible ring- type overrunning clutch is developed. The analysis shows that this overrunning clutch is more suitable for the conditions of high speed and high load,and more easily to design.